Methodological Aspects of the Use of Modern Information and Communication Technologies and Artificial Intelligence in the Teaching of Foreign Languages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the methodological aspects of using modern information and communication technologies (ICT) and artificial intelligence (AI) solutions in foreign language teaching. Based on literature analysis, the effectiveness, application methods, and existing challenges of ICT and AI tools in language teaching are analyzed. Furthermore, the role and prospects of these technologies in improving educational quality are discussed.